2011
DOI: 10.1111/j.1559-1816.2011.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Stages of Change in Physical Exercise and Social Support: An Integrated Socio‐Psycho‐Economic Approach

Abstract: The present research attempts to integrate behavioral and social science theories (e.g., theory of reasoned action, social cognitive theory, transtheoretical model) in assessing the effect and sources of social support of persons in various stages of physical exercise. Using multinomial regression to analyze the data collected via interviews from a sample of over 1,500 working adults in Jamaica, strong statistical support was found for the role of social support in initiating and maintaining exercise. The impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
2
4
0
1
Order By: Relevance
“…Our finding of increased percentages in the action or maintenance stages in this QI project using the social network Facebook was consistent with the literature that helping relationships (also called social support) are important in the preparation stages and for low-SES mothers (Chang et al, 2008;Gibbison & Johnson, 2012;Singer, 2006;SAMHSA, 1999). Our use of theory-based Facebook groups and messaging to improve readiness to participate in an employee wellness program reinforced a finding that Facebook communication promotes participant retention in wellness programs (Maher et al, 2014), although participation and retention are different.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding of increased percentages in the action or maintenance stages in this QI project using the social network Facebook was consistent with the literature that helping relationships (also called social support) are important in the preparation stages and for low-SES mothers (Chang et al, 2008;Gibbison & Johnson, 2012;Singer, 2006;SAMHSA, 1999). Our use of theory-based Facebook groups and messaging to improve readiness to participate in an employee wellness program reinforced a finding that Facebook communication promotes participant retention in wellness programs (Maher et al, 2014), although participation and retention are different.…”
Section: Discussionsupporting
confidence: 90%
“…Tailoring interventions requires effective communication strategies, and theory-based strategies are more effective than strategies not rooted in theory (Korda & Itani, 2013). Helping relationships (also called social support) from family, health care workers, and friends are especially important in the preparation stages when starting an exercise program (Gibbison & Johnson, 2012; Substance Abuse and Mental Health Services Administration [SAMHSA], 1999). Organized social support can provide critical support for people in the preparation stage to advance to action (Singer, 2006).…”
Section: Review Of Relevant Literature To Guide Our Programmentioning
confidence: 99%
“…It is important to note that individuals may not necessarily proceed through each of the five stages in a linear fashion. In most cases, individuals will stagnate in one stage for an extended period of time or even revert to earlier stages in the process (Gibbison and Johnson 2012;Lamb and Joshi 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Cognitive factors including consciousness raising are more prevalent during earlier stages, whereas behavioral processes such as helping relationships are present during both early and late-stage behaviors. For example, Gibbison and Johnson (2012) found social support, specifically from close friends, to be a critical factor in initiating (preparation stage) and maintaining (maintenance stage) exercise behaviors among adults.…”
mentioning
confidence: 99%
“…Therefore, changing behavior is better conceptualized as a process rather than an event (Prochaska & DiClemente, 1982, 1986). More importantly, this approach demonstrates that people vary dramatically in their attitudes, beliefs, and intention across different stages of change (Bamberg, 2007; Cabral et al., 2004; Gibbison & Johnson, 2012; Glanz et al., 2008; Noar & Stee, 2012). In this respect, scholars have suggested that “persuasive messages and interventions could be uniquely targeted and tailored to the stage of readiness to change that behavior” (Noar & Stee, 2012, p. 210).…”
Section: Introductionmentioning
confidence: 99%